Introduction: Multidimensional Approaches to Address Social Crises Based on Social Justice and Community Empowerment - Mauluddin, Agus; Rozikin, Opik (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2025)
The Volume 7 No. 2 Edition JCIC: Jurnal CIC Lembaga Riset dan Konsultan Sosial (E-ISSN: 2746-5160) is a peer-reviewed journal published by the CIC Lembaga Riset dan Konsultan Sosial in collaboration with Asosiasi Peneliti Ilmu Sosial Indonesia (APISI). The latest issue of JCIC: Jurnal CIC Lembaga Riset dan Konsultan Sosial presents a collection of interdisciplinary studies that highlight contemporary dynamics in society through the lenses of decolonial thought, criminology, law, and socio-ecological practices. Each article in this issue offers novel insights into understanding, responding to, and intervening in complex social challenges.